The Effect of Non-Performing Finance on Return on Assets in Sharia Banking (Case Study of Sharia Banks registered with the Financial Services Authority - Devita Sari (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2024)
The presence of sharia banking over the last two decades has made the economy more advanced, which can be seen from the institutional and sharia financial services aspects. Customers can choose various sharia banking products at sharia banking. Financial products that adhere to Islamic sharia are known as sharia banking products. The prohibition of usury (interest) and business practices based on Islamic sharia are the main principles of Islamic banking. Fund collection, distribution and service products are examples of sharia banking products.This research is quantitative. The population in this assessment are Islamic business banks registered with the Money-Related Organization Authority, so there are 14 Islamic business banks, this observation is PT. Bank Muamalat Indonesia Tbk, PT. Bank Mega Syariah Tbk, and PT. Bank BCA Syariah Tbk. 2. Hypothesis test results showed that the t-calculated value of flexible Non Performing Finance (NPF) had an impact on Return On Assets (ROA) where the t-calculated value reached 5.751 > from the t-table of 2.04841 so that the exploration results received Ha.The results of the Coefficient of Determination state that the Non-Performing Finance (NPF) variable can contribute or can express flexible Return On Assets (ROA) as much as 49.7% (0.497x100%=49.7%) but more than 50.3% (100%- 49 .7%=50.3%) is stated in flexible outside the exploration model.